Approved drugs ezetimibe and disulfiram enhance mitochondrial Ca2+ uptake and suppress cardiac arrhythmogenesis. (18th August 2021) - Sander, Paulina; Feng, Michael; Schweitzer, Maria K.; Wilting, Fabiola; Gutenthaler, Sophie M.; Arduino, Daniela M.; Fischbach, Sandra; Dreizehnter, Lisa; Moretti, Alessandra; Gudermann, Thomas; Perocchi, Fabiana; Schredelseker, Johann
Abstract : Background and Purpose: Treatment of cardiac arrhythmia remains challenging due to severe side effects of common anti‐arrhythmic drugs. We previously demonstrated that mitochondrial Ca 2+ uptake in cardiomyocytes represents a promising new candidate structure for safer drug therapy. However, druggable agonists of mitochondrial Ca 2+ uptake suitable for preclinical and clinical studies are still missing. Experimental Approach: Herewe screened 727 compounds with a history of use in human clinical trials in a three‐step screening approach. As a primary screening platform we used a permeabilized HeLa cell‐based mitochondrial Ca 2+ uptake assay. Hits were validated in cultured HL‐1 cardiomyocytes and finally tested for anti‐arrhythmic efficacy in three translational models: a Ca 2+ overload zebrafish model and cardiomyocytes of both a mouse model for catecholaminergic polymorphic ventricular tachycardia (CPVT) and induced pluripotent stem cell derived cardiomyocytes from a CPVT patient. Key Results: We identifiedtwo candidate compounds, the clinically approved drugs ezetimibe and disulfiram, which stimulate SR‐mitochondria Ca 2+ transfer at nanomolar concentrations. This is significantly lower compared to the previously described mitochondrial Ca 2+ uptake enhancers (MiCUps) efsevin, a gating modifier of the voltage‐dependent anion channel 2, and kaempferol, an agonist of the mitochondrial Ca 2+ uniporter. Both substances restored rhythmic cardiac contractions in a zebrafish cardiac arrhythmia model and significantly suppressed arrhythmogenesis in freshly isolated ventricular cardiomyocytes from a CPVT mouse model as well as induced pluripotent stem cell derived cardiomyocytes from a CPVT patient. Conclusion and Implications: Taken together we identified ezetimibe and disulfiram as novel MiCUps and efficient suppressors of arrhythmogenesis and as such as, promising candidates for future preclinical and clinical studies.